2017
DOI: 10.1186/s12910-017-0180-2
|View full text |Cite
|
Sign up to set email alerts
|

Presumed consent: licenses and limits inferred from the case of geriatric hip fractures

Abstract: BackgroundHip fractures are common and serious injuries in the geriatric population. Obtaining informed consent for surgery in geriatric patients can be difficult due to the high prevalence of comorbid cognitive impairment. Given that virtually all patients with hip fractures eventually undergo surgery, and given that delays in surgery are associated with increased mortality, we argue that there are select instances in which it may be ethically permissible, and indeed clinically preferable, to initiate surgica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…From a legal standpoint, patients have decisional capacity when they understand all of the relevant information, are able to appreciate the current situation and its consequences, and are able to manipulate this information in a rational manner 51 . While many patients may at first seem like they are able to consent, the use of probing questions often reveals substantial cognitive issues that may preclude the ability to provide informed consent 28,29,52 . When there is doubt regarding decisional capacity, a geriatrician can help with the assessment.…”
Section: Qolmentioning
confidence: 99%
“…From a legal standpoint, patients have decisional capacity when they understand all of the relevant information, are able to appreciate the current situation and its consequences, and are able to manipulate this information in a rational manner 51 . While many patients may at first seem like they are able to consent, the use of probing questions often reveals substantial cognitive issues that may preclude the ability to provide informed consent 28,29,52 . When there is doubt regarding decisional capacity, a geriatrician can help with the assessment.…”
Section: Qolmentioning
confidence: 99%
“…The pervasive nature of cognitive impairment among older patients with fragility fractures renders the assessment of decision making capacity a necessity. 3 Studies have reported prevalence of known dementia in adults over the age of 65 suffering from hip fractures at 28% with an additional 8% diagnosed upon presentation. 3 , 4 Prevalence of cognitive impairment in geriatric orthopaedic trauma patients has also been recorded at 35.1%.…”
Section: Introductionmentioning
confidence: 99%
“… 3 Studies have reported prevalence of known dementia in adults over the age of 65 suffering from hip fractures at 28% with an additional 8% diagnosed upon presentation. 3 , 4 Prevalence of cognitive impairment in geriatric orthopaedic trauma patients has also been recorded at 35.1%. 5 Obtaining a formal assessment in elderly orthopaedic trauma patients not only identifies patients with cognitive impairment but also provides physicians with data to support and uphold patient autonomy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…That restaurant visit made me wonder if there is a role for surgical informed consent, omakase style as well. In this model, patients can state some general preferences-a willingness to take some risk for a faster recovery, say, or a particular dislike of immobilization-but beyond that, the details of the care are left to the surgeon's experience, expertise, and best judgment, just as they'd be used in an emergency setting [4].…”
mentioning
confidence: 99%